2014
DOI: 10.1016/j.lungcan.2014.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in lung cancer incidence rates and trends by histologic type in the United States, 2004–2009

Abstract: Objective The examination of lung cancer by histology type is important for monitoring population trends that have implications for etiology and prevention, screening and clinical diagnosis, prognosis and treatment. We provide a comprehensive description of recent histologic lung cancer incidence rates and trends in the U.S. using combined population-based registry data for the entire nation. Materials and Methods Histologic lung cancer incidence data was analyzed from CDC’s National Program of Cancer Regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
126
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(150 citation statements)
references
References 44 publications
(43 reference statements)
12
126
1
1
Order By: Relevance
“…The latter two reports highlighted that, although ihc staining might not always be required for nsclc subtyping, it clearly lowers the rate of nsclc nos diagnoses. The results reported by VanderMeer et al 17 are consistent with those from other academic centres and suggest the use of ihc in their cohort, compared with the larger provincial study in which more than 40% of cases were signed out without a pathologic subtype 4 .…”
supporting
confidence: 82%
See 1 more Smart Citation
“…The latter two reports highlighted that, although ihc staining might not always be required for nsclc subtyping, it clearly lowers the rate of nsclc nos diagnoses. The results reported by VanderMeer et al 17 are consistent with those from other academic centres and suggest the use of ihc in their cohort, compared with the larger provincial study in which more than 40% of cases were signed out without a pathologic subtype 4 .…”
supporting
confidence: 82%
“…Of those diagnosed, approximately 85% have non-small-cell lung cancer (nsclc). In that subgroup, approximately 40% have adenocarcinoma histology; 10%-15%, squamous cell carcinoma; and 5%-10%, neuroendocrine carcinoma; the rest are classified as not otherwise specified (nos) [2][3][4] . Recent developments in the therapy and understanding of the pathobiology of lung cancer have triggered a refinement of the histologic classifications to take into account the advent of novel targeted therapies and chemotherapy agents 5 .…”
mentioning
confidence: 99%
“…Globocan 2012 reported an estimated 1.8 million new lung cancer cases in 2012 (12.9% of the total) and 1.59 million deaths, accounting for almost one in five cancer deaths (19.4% of the total) in the world. In most Western countries, lung cancer incidence and mortality rates have been decreasing; in the United States (US), lung cancer incidence significantly decreased among men, although it remained stable among women during 2004–2009 1. In contrast, lung cancer incidence and mortality rates are still increasing in China 1, 2, 3…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, a Japanese study showed the usefulness of AFI for detection of latent airway ischemic damage in pigs that had undergone tracheal autotransplantation, allowing early treatment of the anastomotic site and preventing stricture formation (20). Lastly, AFB may be a recommended procedure in addition with WLB for follow-up in patients with known severe dysplasia or CIS in the central airway (21), helping to guide surgical resection range when necessary, and reducing postoperative recurrence rate.…”
Section: A B Cmentioning
confidence: 99%